Луцьк: місто і соціум у другій половині ХVІ ст. - Shtanko, Oksana; Штанько, Оксана Федорівна (Східноєвропейський національний університет ім. Лесі Українки, 2013)
У розвідці здійснено спробу помістити сферу взаємозв’язків міста та соціуму Луцька другої половини ХVІ ст. в умовну схему грод – магістрат – міська громада. На основі виявлених архівних джерел визначено особливості їхніх відносин у різних проявах – від конфронтації до взаємодії як на особистісно-приватному, так і на колективно-корпоративному рівнях.«The capital city» of Volyn land Lutsk has a proud and rich on events history. The most important period in the town’s history was sixsteenth. It was the time of establishment of a European norms of Magdeburg law, which included removal of the county government under the castle of the city and moving to her own jurisdiction by qualitatively new government - city council. However, even when divided into two parts in the legal sense Lutsk citizens continued to live in the same Lutsk, tackle domestic disputes and problems in Grod or at City Hall, to support or condemn the actions of government officials.
City and Society in Second Half of XVI Century
Keywords: Луцьк; міщани; магістрат; грод; міські урядники; Lutsk; the town community; the magistrate; grod (castle court); town officials